The role of fuzzy logic in the development of Artificial intelligence research In the field of language . - مذكور د. مليكة (lark, 2020)
Absract : Artificial intelligence initially relied on digital language and dual-value logic based on law of non-contradiction and the law of excluded middle ,but the limited of this intelligence in the treatment of vague and loose informations, Which prompted scientists of artificial intelligence to turn to the fuzzy logic, which showed that the fuzziness It should not be excluded, but it must be adopted and invested for precision and clarity. Problematic: How did the fuzzy Logic contributed in the development of Artificial intelligence, especially with the advent of superintelligence research?. Keywords : fuzzy logic, Artificial intelligence, Natural language, Digital language.